ETHICAL THOUGHT IN ISLAMIC PHILOSOPHY: A STUDY OF GHAZALI AND MISKAWAYH - Shohib Muslim; Suhari (Adisam Publisher, 2025)
This research explores the ethical thinking of two major figures in Islamic philosophy, namely Al-Ghazali and Miskawayh. Al-Ghazali, known for his Sufistic approach, emphasised the importance of a spiritual relationship with God as the basis for achieving a moral life and true happiness. Meanwhile, Miskawayh, who was influenced by Aristotelian thought, offered a more rational view by emphasising balance and the use of reason to form good character and achieve virtue. This study found that although the two had different approaches, both spiritual and rational, they complemented each other and made significant contributions to the development of ethics in the Islamic philosophical tradition.